2022
DOI: 10.9734/ijpss/2022/v34i2131330
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Correlation and Path Coefficient Analysis of Brinjal (Solanum melongena L.) for Yield and Yield Contributing Traits

Abstract: Correlation and path analysis was studied for 43 lines and F1s of brinjal (Solanum melongena L.) for seventeen qualitative and quantitative characters. The studies revealed that total fruit yield plant-1 which is the most important trait had highly significant and positive association with fruit weight, number of fruits plant-1, fruit length, fruit diameter and number of pickings plant-1 at both phenotypic and genotypic level. A significant but negative correlation of fruit yield was recorded with days to firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…While negative and non-significant correlation with fruit yield per plant was recorded by plant height and Vitamin-C. Similar findings were recorded by Neha et al (2017) [11] , Saha et al (2019) [14] , Kumar et al (2020) [7] , Vinutha et al (2020) [19] , Nazir et al (2022) [10] , Thangamani and Jansirani (2012) [18] , Ahmed et al (2013) [1] , Prabakaran et al (2015) [13] , Lakshmi et al (2014) [8] and Chandra Shekar et al (2014) [3] . Path coefficient analysis at genotypic level shown in Table 2 and Figure 1.…”
Section: Resultssupporting
confidence: 80%
“…While negative and non-significant correlation with fruit yield per plant was recorded by plant height and Vitamin-C. Similar findings were recorded by Neha et al (2017) [11] , Saha et al (2019) [14] , Kumar et al (2020) [7] , Vinutha et al (2020) [19] , Nazir et al (2022) [10] , Thangamani and Jansirani (2012) [18] , Ahmed et al (2013) [1] , Prabakaran et al (2015) [13] , Lakshmi et al (2014) [8] and Chandra Shekar et al (2014) [3] . Path coefficient analysis at genotypic level shown in Table 2 and Figure 1.…”
Section: Resultssupporting
confidence: 80%
“…Although the number of primary branches per plant had the highest negative direct effect on total fruit yield per plant, it exhibited a high positive indirect effect via total fruit yield per plant (-0.591), leading to a positive correlation with yield. These findings are consistent with those reported by Chotaliya and Kulkarni [13], Gebremichael et al [14], and Kassahun et al [15], Gazala Nazir et al [16].…”
Section: Genotypic Path With Yield Q/hasupporting
confidence: 93%
“…The analysis of variance indicated highly significant differences among the genotypes due to genotypes for all traits viz; Days to first flowering, Days to first fruit set, Days to first fruit picking, Number of branches per plant, Plant height(cm), Plant spread(cm), Fruit length (cm), Fruit diameter (cm), Number of fruits per plant, Average fruit weight (g), Fruit yield per plant (kg), Fruit yield per plot (kg), Fruit yield per hectare (q), Total soluble solids (°Brix), Total Anthocyanin content (mg/100g), Vitamin C (mg/100g), Phenols (mg/100g), Total sugars (%) and Dry matter (%). Same results were found by Hassan et al [4], Madhavi et al [1], Milli et al [5], Praveen et al [6] and Dhaka and Soni [7], Kumar et al [8], Singh et al [9], Ansari et al [10], Gazala et al [11]. Analysis of variance indicated that sufficient variability existed for all these characters and which provide the potential for selection of suitable genotypes having desirable traits for further crop improvement as depicted in Tables 1a, 1b and 1c.…”
Section: Analysis Of Variancesupporting
confidence: 67%
“…Therefore, unpredictability plays a crucial role in determining the quantity of advancement anticipated from selection. A crop's potential for improvement would be greater the more genetic diversity it possessed and keeping the land limitation in mind it is important to improve the yield of brinjal by developing high yielding varieties [3].…”
Section: Introductionmentioning
confidence: 99%